What turns cities into international financial centres? Analysis of cross-border investment banking 2000–2014 - Wojcik, D; Knight, E; Pazitka, V (Oxford University Press, 2017)
Globalisation, financialisation and technology have fuelled competition among international financial centres (IFCs), with investment banks playing an important part in the process. This study introduces novel data on cross-border investment banking revenues in 2000-2014 by city, and investigates their determinants. It shows that IFCs emerge from cities that are already leading domestic financial centres, with large, deep, flexible and open labour markets, and a large and internationalised non-financial sector, in countries with strong rule of law and contract enforcement. Stock market returns, corporate- and finance-specific taxation, English as the official language, and legal family of origin do not seem to matter.